Ultrathin h-BN/Bi2MoO6 heterojunction with synergetic effect for visible-light photocatalytic tetracycline degradation - Du, Zhao; Feng, Lang; Guo, Zhonglu; Yan, Tongqi; Hu, Qi; Lin, Jing; Huang, Yang; Tang, Chengchun; Fang, Yi (Journal of colloid and interface science, 2021)
[Display omitted] Herein, a series of ultrathin h-BN/Bi2MoO6 heterojunction with excellent photocatalytic activity has been firstly prepared via a feasible solvothermal method. Our results suggest that the optimized photocatalyst possesses a high degradation ratio of tetracycline (TC), oxytetracycline (OTC) and doxycycline (DC) up to 99.19%, 95.28% and 91.04% under visible-light irradiation, respectively. We highlight that the outstanding photocatalytic activity is mainly attributed to the prominent performance of tetracycline adsorption on h-BN and the dominant visible-light absorption by Bi2MoO6 as well as the effective photogenerated carrier separation induced by the synergetic effect between h-BN and Bi2MoO6. Moreover, DFT calculations reveal that the built-in electric field formed between h-BN and Bi2MoO6 gives rise to the separation of carriers and the polarization of tetracycline molecules. Last but not the least, the specific process and micro-mechanism of the photocatalytic tetracycline degradation under visible-light driven have also been illuminated. The present work pioneers the application of ultrathin h-BN/Bi2MoO6 heterojunction as a novel tetracycline degradation photocatalyst and further guides the design of more visible-light photocatalysts.